2020
DOI: 10.2478/ctra-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Association, Overlap, and Inhibition: A Study of Implicit Theories of Creativity

Abstract: After more than six decades of systematic study of creativity, there is still no agreement regarding components essential to define creativity. Prior studies of implicit and explicit theories have suggested adding criteria to the standard definition of what creativity is; however, an alternative approach is to explore what creativity is not. The current investigation aimed to study both perspectives. The social validation method was employed in Study 1 (an open-ended questionnaire) to identify laypeople’s noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…implications This study reveals the need to reconsider the rationale and goals of the Arts and Creativity learning area within Hong Kong's official Curriculum Guide (CDC, 2017). As explained in the Introduction, creativity in the arts involves several recursive components that require exploration, discovery, experimentation, and ultimately time and freedom (Abdulla Alabbasi et al, 2020;Campbell & Scott-Kassner, 2019;Fox & Schirrmacher, 2015). However, the QR reports suggest that Hong Kong kindergartens cannot guarantee the basic conditions for creativity to emerge, due to multiple factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…implications This study reveals the need to reconsider the rationale and goals of the Arts and Creativity learning area within Hong Kong's official Curriculum Guide (CDC, 2017). As explained in the Introduction, creativity in the arts involves several recursive components that require exploration, discovery, experimentation, and ultimately time and freedom (Abdulla Alabbasi et al, 2020;Campbell & Scott-Kassner, 2019;Fox & Schirrmacher, 2015). However, the QR reports suggest that Hong Kong kindergartens cannot guarantee the basic conditions for creativity to emerge, due to multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…Western ECE scholars have defined the notion of creativity in terms of "originality, imagination, divergent thinking, and the ability to create something new or to combine things in novel but meaningful ways" (Essa & Burnham, 2019, p. 214). Scholars focusing on different art forms concur in that fostering creativity in the arts requires three recursive components: (a) exploration and/or discovery of elements pertaining to the art form at hand; (b) experimentation and/or improvisation with said elements; and (c) creation, composition, and/or performance of original final products (Abdulla Alabbasi et al, 2020;Campbell & Scott-Kassner, 2019;Fox & Schirrmacher, 2015).…”
Section: Conceptual Framework: Western Perspectives On Arts and Creat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the decades, the scientific research on creativity and the creative process has shown the function of navigating complex challenging thoughts (Abdulla Alabbasi et al, 2020;Furnham et al, 2008;Kaugman & Gregoir, 2016;Kaufman & Kaufman, 2009;Runco, 2014). Creative processes allow us to navigate complexity, contradictions, and multiple points of view (Barron, 1969).…”
Section: Creative Processmentioning
confidence: 99%